A monolithically integrated torsional CMOS-MEMS relay. (5th October 2016) - Riverola, M; Sobreviela, G; Torres, F; Uranga, A; Barniol, N
Abstract: We report experimental demonstrations of a torsional microelectromechanical (MEM) relay fabricated using the CMOS-MEMS approach (or intra-CMOS) which exploits the full foundry inherent characteristics enabling drastic reduction of the fabrication costs and batch production. In particular, the relay is monolithically integrated in the back end of line of a commercial standard CMOS technology (AMS 0.35 μ m) and released by means of a simple one-step mask-less wet etching. The fabricated torsional relay exhibits an extremely steep switching behaviour symmetrical about both contact sides with an on-state contact resistance in the k Ω -range throughout the on-off cycling test.